The influence of a porn literacy intervention on explicit and implicit attitudes - Marina F. Thomas; Moniek Buijzen (Studies in Communication, Media)
Mainstream pornography presumably influences explicit and implicit attitudes. This study presents a media literacy intervention specifically for pornography in form of a short video (3 min.) highlighting that pornography is effortfully constructed. After exposing 80 adults between 18 and 33 (60% female) to mainstream pornography, it was experimentally tested if the porn literacy intervention (compared to a matched control video) decreased perceived porn realism, undesired explicit and implicit attitudes, and whether the influence of the intervention was moderated by sexual experience and prior porn use. The preregistered experiment showed that the porn literacy intervention had no effect on perceived realism of pornography, body dissatisfaction, implicit sexism, or explicit and implicit attitudes toward condom use (all materials, data, and analysis scripts available at https://osf.io/2pk5e/). Explicit sexist attitudes were decreased in individuals with few sex partners and increased in individuals with mean or higher prior porn use. The intervention influenced self-reported sexism but not the presumed mechanism perceived realism (associated with younger age). Across conditions, participants were neither more dissatisfied with their bodies nor more dismissive toward condoms after watching mainstream porn; sexist attitudes were even lower at posttest. The study proves the need for more research clarifying what, how, and when we learn from porn, including more theoretical refinement in media literacy theory with its mechanisms, its application to pornography, and concrete interventions.